Single peritoneal dialysis centre observations of treatment adequacy, anemia treatment, inflammation, mineral bone disease, and peritonitis rate – In patients undergoing continuous ambulatory peritoneal dialysis versus automated peritoneal dialysis - Maša Knehtl; Martin Hren; Nina Hojs; Sebastjan Bevc; Radovan Hojs; Robert Ekart (Acta Medico-Biotechnica, 2021)
Purpose: Peritoneal dialysis was introduced to our centre in 1998. The aim of our retrospective analysis was to evaluate the difference in treatment adequacy, erythropoietin requirements, serum haemoglobin, serum C–reactive protein (CRP) and serum intact parathyroid hormone (i–PTH) levels, and episodes of peritonitis in patients switching from continuous ambulatory peritoneal dialysis (CAPD) to automated peritoneal dialysis (APD). We introduce peritoneal dialysis as a method of treatment for end–stage renal disease and the results of a retros-pective analysis.Methods: From May 1998 to December 2013, we retrospectively reviewed 12 patients (9 males and 3 females; mean age, 52.8±11.7 years) who switched from CAPD to APD. According to the peritoneal equilibration test, 75% of the patients were high transporters. We compared thetwo periods regarding peritoneal treatment adequacy number (Kt/V), erythropoietin requirements, serum haemoglobin, and CRP and i–PTH levels. We analysed the episodes of peritonitis during the CAPD and APD periods.Results: The average time spent on CAPD was 747.1±1028.2 days, and the average time spent on APD was 1300.0±1042.0 days. For the CAPD period, the mean Kt/V was 2.13±0.43, the mean haemoglobin value was 117.8±6.2 g/l, the mean erythropoietin requirement was 5290.1±4641.4 IU/week, the mean CRP value was 8.7±9.3 mg/l, and the mean i–PTH value was 580.2±445.9 pg/ml. For the APD period, the mean Kt/V was 2.24±0.35, the mean haemoglobin value was 117.1±8.6 g/l, the mean erythropoietin requirement was 4829.9±4976.6 IU/week, the mean CRP value was 9.1±8.3 mg/l, and the mean i–PTH value was 550.5±400.0 pg/ml. When comparing the two treatment modalities with a paired samples test, we found no significant differences regarding time spent (p=0.273), Kt/V (p=0.159), haemoglobin concentration (p=0.804), erythropoietin requirements (p=0.303), and CRP (p=0.886) and i–PTH levels (p=0.802). Further, no difference in the rate of peritonitis episodes between both modalities was found.Conclusion: Both peritoneal dialysis modalities are equal with respect to treatment adequacy, erythropoietin requirements, serum haemoglobin concentration, CRP and i–PTH levels, and peritonitis episodes.